Conjugation problem about jointly separate flow of viscoelastic and viscous fluids in the plane duct - Korzyuk, V. I.; Lemeshevsky, S. V.; Matus, P. P.; Shalima, V. N. (Mathematical Modelling and Analysis, 1999)
Conjugation problem about jointly separate flow of viscoelastic and viscous fluids in the plane duct is considered. The results concerning of solvability of this problem are presented. The implicit difference scheme for the conjugation problem is constructed. The consistency conditions are approximated with the second order of approximation with respect to spatial variable. The convergence of the suggested difference scheme is investigated by method of energy inequalities.Sujungimo uždavinys, aprašantis bendrą klampaus ir klampiaielastingo skysčių tekėjimą plokščiuose kanaluoseSantrauka. Nagrinėjamos sujungimo sąlygos, kai liečiasi klampus ir klampiai elastingas skysčiai. Ištirtas diferencialinio uždavinio išsprendžiamumas. Uždavinys aproksimuojamas neišreikštine baigtinių skirtumų schema. Suderinamumo sąlygos aproksimuojamos antrosios tikslumo eiles diskrečiuoju analogu. Energetinių nelygybių metodu įrodomas baigtinių skirtumų schemos sprendinio konvergavimas ir įvertinamas konvergavimo greitis.First Published Online: 14 Oct 2010